If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -6 = 3x + 10 Reorder the terms: -6 + -5x = 3x + 10 Reorder the terms: -6 + -5x = 10 + 3x Solving -6 + -5x = 10 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + -5x + -3x = 10 + 3x + -3x Combine like terms: -5x + -3x = -8x -6 + -8x = 10 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + -8x = 10 + 0 -6 + -8x = 10 Add '6' to each side of the equation. -6 + 6 + -8x = 10 + 6 Combine like terms: -6 + 6 = 0 0 + -8x = 10 + 6 -8x = 10 + 6 Combine like terms: 10 + 6 = 16 -8x = 16 Divide each side by '-8'. x = -2 Simplifying x = -2
| 7y+2(y-5)=5(y+1)-4 | | 2(x+97)=2x+17 | | f(x)=3x+2 | | 4x+8-6x+12=180 | | 14-x^2= | | 9r-2=4r+9 | | 3a-1.5=-5.25 | | (3/4)w+8=(1/3)w-7 | | 3/4x-1/2=4 | | (1/2)w+7=(2w)-2 | | 84-x=84-x | | 1=-2x+7 | | 2=-2x+7 | | Ifx=110findy | | 4(x+2)-3whenx=6 | | 8x-14=2x+54 | | 13-6(a+2)=8+a | | -2=-4x-3 | | 2x+60=8x | | -2(x-5)-21=-11 | | -7x^4+56x^3+9x^3+(-72x^2)+3x^2+(-24x)= | | (2x)/5+1/3=(7x-2)/15 | | 10p-7=63 | | 18=-3(3x-6) | | 3x-6=4x+3 | | 6y-2=4y-18 | | 5(3+5x)-4=161 | | 39x^2+55x+12=0 | | 4(x-3)-16=x+9 | | 5=x^2-3x-2 | | 3.4x-0.88=1.36-2.2x | | 4(x-16)-3=4x-67 |